Mancha da gluma do trigo : efeito em componentes de rendimento e controle genético da resistência - Mühl, Fabiana Raquel (2006)
Stagonospora nodorum blotch, caused by Stagonospora nodorum is a disease that can induce high yield losses and reduce wheat grain quality. In Brazil, the disease may impose annual yield losses from 10 to 30% of susceptible cultivars. The disease may affect grain yield since the very first growths stages up to plant maturity. Cultural practices as crop rotation and fungicide spraying as well as the use of resistant cultivars can be used for disease control but resistant varieties seems to be the least expensive and most environment safe. The objective of this work was to evaluate the effect of the disease on yield components and study the inheritance of resistance to Stagonospora nodorum blotch of wheat under controlled environment and field conditions. The parents, F1 and F2 progenies of the crosses BR 32 x FCEP 29, BR 32 x PF 990606, BRS 194 x FCEP 29, BRS 194 x PF 990606 their reciprocals were sowed in greenhouse and in the field at Embrapa experimental area and the plants were inoculated with S. nodorum for disease evaluation. Under controlled environment, the pathogen was inoculated to plants with a 10 conidia per mL suspension, in a growth chamber with temperature adjusted to 22º C and air moisture of 90%, in a photoperiod of 12 hours, during a 48 hour period. The plants were sprayed until run-off. The wheat variety BRS 194 displayed the lowest disease severity (3% to 8%), independently of growth stage in which the plants were inoculated. However, CD 105 a susceptible variety showed the highest values of glume blotch severity (34% to 66%), depending in which growth stage plants were inoculated. Nevertheless, BRS 49 witch behaved as a moderately susceptible variety showed 31 to 37% of disease severity. The severity of the disease was estimated based on leaf necrosis. The herdability in a broad sense was estimated in 63% to 77% for crosses studied in greenhouse, but for crosses studied under field conditions the herdability values were estimated in 77% to 87%. The diagrams of plant frequency distribution of disease severity in each generation indicated a continuous variation, apparently controlled by several genes of small effect. The analysis of mean components using the additive-dominant model with three parameters suggested a greater additive effect regarding disease resistance in most of the crosses